THE CORRELATION BETWEEN QUIZIZZ APPLICATION, READING INTEREST, AND READING COMPREHENSION OF CLASS XI STUDENTS OF SMK BAKTI MANDIRI BEKASI - Hani Hastari; Safari Safari (Lingua, 2022)
This study investigated the correlation between Quizizz application, reading interest, and reading comprehension of class XI students of SMK Bakti Mandiri Bekasi. However, the use of Quizizz application is still in primary and secondary schools. Therefore, the study tries to use Quizizz to create a new learning situation and see how well that worked out in SMK while in SMK is limited and the use of Quizizz application in reading too little. This study was aimed at finding out whether or not a significant correlation between Quizizz application and their reading interest, the correlation between Quizizz application and their reading comprehension, and the correlation between students’ reading interest and their reading comprehension. The population of this study was 31 students of class XI Akuntansi A SMK Bakti Mandiri Bekasi. The design of the study was correlational in a quantitative approach. To collect data, the researcher used questionnaire and test. The data was analyzed with Pearson product-moment correlation. Based on the data analysis, it was found that: first, Sig. 0,332 that bigger than 0,05 means there is no correlation between Quizizz application and their reading interest, second, Sig. 0,49 that bigger than 0,05 means there is a correlation between Quizizz application and their reading comprehension, third, Sig. 0,045 is bigger than 0,05 which means there is a correlation between students’ reading interest and their reading comprehension.